Criaturas bien nacidas aunque mal habidas y bien habidas aunque mal nutridas. - Agustín Grajales (Nuevo mundo - Mundos Nuevos, 2008)
Based on 12 396 baptisms of legitimate, natural and abandoned children of the parish of El Sagrario of the cathedral of the city of Puebla from 1783 to 1792, the rates of illegitimacy are analyzed by ethnic group (between eight and twenty percent) as well as the abandonment of children. This practice was carried out on the door steps of the individual's homes and to a lesser extent in the House of Foundling Children, of which its origin and scope is mentioned. The study approaches the differences according to the genre and the motivations: shortage of resources and the protection of the honor of the mother. A better understanding of the problem was achieved as a result of the analysis of a single letter of mercy that appeared among 1 389 registers; it is a question of an extraordinary document for the content of the speech and the rarety of its existence.